KAJIAN REKAYASA LALU LINTAS PADA PENEMPATAN KINERJA PARKIR BADAN JALAN DI PASAR TRADISIONAL - Mekar Ria Pangaribuan (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2018)
Along with the increase of transportation facilities, resulting in an increase in the volume of traffic in traditional markets, which can cause problems how to park vehicles that can meet all the vehicles coming, so that traffict flow can still smooth and orderly. Purwodadi market is located in the middle of the shopping and seetlement, with pass by 4 segment of road, will be done traffic engineering to know how big influence of parking at of road body which can influence road road performance in order not to experience jam, aspecially at rush hour. The objectives of the research are: 1) to find out how much impact of parking on the road body to the capacity of road service in Purwodadi market, and 2) to know the performance of Purwodadi market street with the parking of the road body. The result of this research is the average volume of traffic per segment passing trought Purwordadi Market is 5,106,70 SMP / hour on segment I, 2,412,30 SMP / hour in segment II, 2,929,35 SMP / hour in segment III and 718,50 SMP / hour in segment IV. While the degree of saturation per each segment is: in segment I with LHR 555.63 kend / jam, segment II LHR 253.92 kend / jam, LHR segment III 0f 307.93 kend / jam, and segment IV is LHR 79.83 kend / jam. The road service level obtained from the degree of saturation (DS) for the level of service road segment I, II and IV including class A, with high-speed load current condition, the driver can choose the desired speed without a hitch, where the value of road performance ratio is not affected the road capacity but influenced the speed of the vehicle. While in segment III the level of service road including class B, the current is stable but the speed of operation began to start limited by traffic, the driver has enough freedom to choose the speed.